Diseño de sistema basado en reglas para apoyar la toma de decisiones de la población en la obtención de los medicamentos. - Pérez Aguada, Darianis; Milanés Luque, Maidelis; Mar Cornelio, Omar; Orellana García, Arturo (Revista Cubana de Informática Médica)
In Cuba, access to pharmaceutical services by the population is affected by the nonavailability of medicines and the remoteness of pharmacies. The lack of information about the existence of medicines and the quantity of these in the network of pharmacies close to a geographical location, coupled with the low supply of medicines and the quality of service provision, generates discontent and nonconformity in the population. In the present investigation, a design is carried out to improve the problem raised from a system based on rules as an aid to decision-making to obtain medicines by the population. A case study is applied through which it is possible to suggest to the user the 5 closest pharmacies where the patient can acquire the medicines on the decisions made.